Differential seedling regeneration patterns across forest–grassland ecotones in two tropical treeline species (Polylepis spp.). (25th March 2018) - Morales, Laura V.; Sevillano‐Rios, Cristian Steven; Fick, Stephen; Young, Truman P.
Abstract: Successful forest expansion into grassland can be limited by seed dispersal and adverse conditions for tree seedlings in the grassland environment. In the high‐elevation Andes, human‐induced fragmentation has exacerbated the patchy distribution of Polylepis forests, threatening their unique biological communities and spurring restoration interest. Studies of Polylepis forest extent in Peru suggest that forest borders have remained stable over the past century despite decreasing anthropogenic disturbance, suggesting that tree seedling recruitment is being limited in the open grassland habitat. We studied natural seedling dispersion patterns of Polylepis sericea and Polylepis weberbaueri (Rosaceae) at forest–grassland edges across a range of environmental conditions to examine seedling recruitment and colonization of grasslands in Huascaran National Park (Peru). Using data from 2367 seedlings found in 48 forest–grassland edge plots (15 m × 15 m) at forest patches between 3900–4500 masl, we employed generalized mixed modelling to identify the significant associations of seedling densities with environmental covariates. In addition, we compared these associations to patterns of adult presence on the landscape. Seedling densities were associated with a combination of variables varying within (distance to forest edge) and among (elevation and dry season solar irradiation) plots across the landscape. For both species, seedling densities decreased with increasing distance away from the forest in a manner consistent with short‐distance seed dispersal by wind. Our results suggest that such short‐distance dispersal may slow forest expansion, but that there also appear to be substantial post‐dispersal limitations to seedling establishment in the grassland. Polylepis sericea densities decreased with elevation, while P. weberbaueri increased with elevation and decreased with solar irradiation. Associations of adult presence with elevation and solar irradiation mirrored those of seedling densities. Management of areas with forest patches dominated by these species should consider these differences in their environmental tolerances, particularly during species selection and zonation for reforestation.